Boundary element analysis of effects of holes in fiber metal laminates - Gan, Bok Sheng (2009)
Fiber metal laminate (FML) is a new class of structural material that is getting more popular in the aerospace industry due to its high strength-to-weight ratio which enables high potential in reducing total weight and thus reducing costs in the structure. FML possessed high fatigue resistance due to its fiber bridging capabilities, which makes it even more attractive as structural materials in the aerospace industry. It is also well known that introducing holes behind a crack impedes crack propagation significantly. In addition, this method of reducing the stress intensity factor at the crack tip also allows total weight reduction in a structure which may prove to be useful in the aerospace industry.